Assessment of iron content of cooking water on bulgur by determining chemical, mineral, colour, textural and thermal characteristics - Michel, Sadiye; Bayram, Mustafa (Wiley, 2024)
BACKGROUNDBulgur, a whole wheat product, has attracted attention in the world in recent years because of its wide usage possibility in different meals. The basic ingredients in bulgur production are wheat and water. The influence of water composition on bulgur quality has not been investigated. Iron in water can cause discolouration in foods by oxidizing and reacting with phenolic compounds and also by hardening the structure of the foods. Therefore, in the present study, the effects of the iron content of water on the quality of bulgur were examined.RESULTSThe effect of the amount of iron in water on bulgur quality was carried out and examined using water containing iron at three different levels (0, 1 and 2 ppm). Using water containing 2 ppm iron in bulgur production caused a decrease in the L* value and an increase in the YI (i.e. yellowness index), thus negatively affecting the colour of the bulgur. In bulgur prepared with water containing 2 ppm iron, the antioxidant activity was also dramatically reduced.CONCLUSIONThe iron content in the water used in bulgur production did not have a negative effect on bulgur quality up to 2 ppm. The protein, ash, phenolic and mineral amounts and textural characteristics of bulgur were not affected by the concentration of iron in the water. As a result, high iron concentration in cooking water negatively affects bulgur's colour and antioxidant activity. Therefore, it is recommended to use iron-free water in bulgur production. (c) 2024 The Authors. Journal of The Science of Food and Agriculture published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.
Keywords: wheat; bulgur; iron; cooking; drying; colour